THE IMPORTANCE OF HYGIENIC EDUCATION IN THE FORMATION OF A HEALTHY LIFESTYLE FOR CHILDREN - Mirzaeva M. M. (Web of Journals Publishing, 2024)
One of the important constituent parts of the healthy lifestyle of the population is the education of high sanitary culture, which is of great importance to the state. The leading place in the formation of sanitary culture is occupied by a set of measures and activities on hygienic education and training.